Non-destructive fiber Bragg grating based sensing system: Early corrosion detection for structural health monitoring - Tan C.H.; Mahamd Adikan F.R.; Shee Y.G.; Yap B.K. (Elsevier B.V., 2023)
Alkalinity; Bragg gratings; Coatings; Corrosion; Corrosion rate; Electric sensing devices; Fiber optic sensors; Hydrogels; Microchannels; Pulse width modulation; Steel corrosion; Steel fibers; Strain rate; Structural health monitoring; Bragg wavelength shift; Corrosion detection; Environment conditions; Fiber Bragg Grating Sensors; Mechanical expansion; pH-sensitive hydrogel; Real time monitoring; Sensitivity performance; Fiber Bragg gratings